UNDERSTANDING THE INTERRELATIONSHIPS AMONG RISK BEHAVIOUR, LEARNING AND MARKET ORIENTATIONS IN INTERNATIONAL BUSINESS RELATIONSHIPS - ., Sulhaini (Journal of Management and Business, 2011)
This paper aims to provide understandings on the interrelationships among risk behaviour, learning orientation and market orientation and business relationship development. This paper was developed based on a qualitative study of six British firms exporting to the Indonesian market. Data was collected through a series of in-depth interviews carried out in UK and Indonesia. The finding was established through a hermeneutic process. The exploration provides an understanding that risk behaviour, learning and market orientations are interrelated and they explain the fluctuation of relationship elements and thus the development of relationship between the British exporters and Indonesian Importers. Learning orientation has a greater role as it also influences the development through market orientation and risk behaviour. The discussion suggests that a company with a better learning orientation will have a better market orientation, become a risk taker and a better ability to develop business relationships.